Implementation of Permenkes Number 1691 the Year 2011 Concerning Patient Safety in Palu Undata Hospital - Hijrianto, Hijrianto; Sudirman, Sudirman; Kadri, Abdul (Universitas Muhammadiyah Palu, 2020)
Implementation of Patient Safety is the obligation of the hospital to fulfill the rights of patients to be free from injury and potential injury (disease, physical/social psychological injury, disability, and death) involving health workers/officers (medical, paramedical) and non-medical, to work together to improve patient safety. The researcher aims to determine the implementation of patient safety at the Update Hospital Palu, as regulated in Permenkes number 1691 of 2011. The type of research used is qualitative, namely observation, interviews, and documentation. The results showed that some health workers/health workers still ignored informed consent/consent for small but risky actions in carrying out their duties. Incidents that occur due to equipment that does not meet standards should be facilitated by KMKP (Patient Safety Quality Committee) at Update Hospital Palu but have not been implemented, but only reduce incidents that occur due to medical personnel errors/paramedics. The need to build individual awareness of staff/officers in carrying out their duties, the need to integrate if there is an incident either due to equipment or due to an error of the officer in one container, namely KMKP Hospital as a report to be evaluated.